Dynamic Frequency Scaling of a Single-Core Processor Using Machine Learning Paradigms. (4th August 2020) - Thethi, Sukhmani K; Kumar, Ravi
Abstract: Dynamic frequency scaling (DFS) is one of the most important approaches for on-the-fly power optimization in modern-day processors. Owing to the trend of chip size shrinkage and increasing the complexity of system design, the problem of achieving an efficient DFS depends upon multi-parametric, non-linear optimization. Hence, it becomes extremely important to identify an optimal underclocking frequency on-the-fly, which depends upon numerous parameters that do not share direct relationship amongst each other. This paper proposes a machine learning approach to DFS of a ubiquitous single-core processor. Several performance parameters of the processor were monitored under an application of a number of clocking frequencies. The dataset thus generated was used to train four artificial neural networks (ANNs) viz. generalized regression (GRNN), decision tree classifier, random forest classifier and backpropagation technique. Under changing parametric conditions of the proposed network, the modes were fit to data while running three applications, i.e. 64- and 1024-point fast fourier transform (FFT) and basicmath applications. The performance of all ANNs was found to be promising and good generalization was obtained with all datasets. In the view of optimizing both speed and power of a system, the results indicate towards suitability of trained GRNN for on-chip deployment for implementing DFS.